Building a Qurani Society: A Collaborative Community Base Research - Slamet Riyadi; Febby Adinda; Febrianti Dewi; Hazimah; Kharismahate Bengi; Miftahussa’adah Irfani; Sri Utari (ASSUNNAH PRESS, 2022)
Pondok Tahfidz Quran Huurun'Iin is a non-formal educational institution specifically for girls, which is located on Jalan Masjid al-Barokah, Marindal I 19B, Deli Tua Timur, Deli Serdang, North Sumatra. Built-in January 2021 in a Muslim-majority environment, however, it seems far from Islamic values. Concern for the condition of the community around the location, especially the younger generation, has encouraged Pondok Tahfidz Quran Huurun'Iin to fill the role of Quran education through non-formal channels. This potential encourages the STAI As-sunnah Arabic Language Education study program to collaborate with Pondok Tahfidz Quran Huurun'Iin in a community service program with the theme